Girls and women in classical Greek religion - Dillon, Matthew, 1963- (Routledge, 2002)
It has often been thought that participation in fertility rituals was women's most importnat religious activity in classical Greece. Matthew Dillon's wide-ranging study makes it clear that women engaged in numerous other rites and cults, and that.